Effects of backbone cyclization on the pharmacokinetics and drug efficiency of the orally active analgesic conotoxin cVc1.1 - Aaron G. Poth; Francis C.K. Chiu; Sofie Stalmans; Brett R. Hamilton; Yen-Hua Huang; David M. Shackleford; Rahul Patil; Thao T. Le; Meng-Wei Kan; Thomas Durek; Evelien Wynendaele; Bart De Spiegeleer; et al. (Elsevier, 2021)
Chronic pain is an undertreated epidemic affecting quality of life in at least 20% of the global population, and CNS-related side effects, tolerance, and addiction are common features of current medications. α-Conotoxin Vc1.1 potently elicits prolonged analgesia in preclinical chronic constriction injury and chronic visceral hypersensitivity models of neuropathic pain. A backbone-cyclized variant, cVc1.1, exhibits superior in vitro stability and is orally active, but its in vivo half-life and disposition, both critical in informing drug candidate progression, remain unexplored. Here, we investigate the pharmacological influence of the peptidic bridge differentiating linear and cyclic Vc1.1 in various preclinical PK/PD rodent models. While previous in vitro studies had indicated cyclization conferred increased stability for cVc1.1, in vivo the peptides exhibited similar half-lives and oral bioavailabilities. The ratios of free drug exposure metrics (Cmax × fu,p and AUC0-inf × fu,p) following oral dosing vs. their respective in vitro IC50s at the GABAB receptor were comparable for Vc1.1 and cVc1.1, indicating similar drug efficiency indexes. MALDI imaging, radiolabel, and LC-MS biodistribution studies of cVc1.1 in rodents demonstrated that the intact cyclopeptide and several metabolites persist in the GI tract for at least 4 h, long after the plasma levels of the intact peptide had fallen below the target IC50. Biodistribution analyses of IV administered 125I-labelled cVc1.1 revealed accumulation primarily in the kidneys consistent with renal elimination, and combined with insignificant uptake in brain, suggested a low likelihood of CNS-related side effects.